Hazard Analysis of Fixed‐Tube‐Sheet Shell‐and‐Tube Heat Exchangers. Issue 5 (29th March 2022) - Rößler, Felix; Krumova, Veronika; Gewald, Stefan; Bauernfeind, Alexander; Freko, Pascal; Thomas, Ingo; Zander, Hans‐Jörg; Rehfeldt, Sebastian; Klein, Harald
Abstract: Fixed‐tube‐sheet shell‐and‐tube heat exchangers (FTHEs) are widely used in process plants to enhance energy efficiency and to control temperature levels of unit operations. Even moderate temperature differences between shell and tube bundle of FTHEs can lead to failure mechanisms induced by thermal stress. To avoid equipment failure, design codes require an analysis of the transient response of an FTHE during special operating conditions. This work presents a modular‐hierarchical approach for the dynamic simulation of FTHEs, which is applied to special operating scenarios such as a loss of tube‐side flow, a shell‐side steaming‐out (cleaning procedure to remove hydrocarbon residues with steam) and a reactor trip (sudden stop of exothermic reaction). Abstract : Fixed‐tube‐sheet shell‐and‐tube heat exchangers (FTHEs) are widely used in process industry to control temperature levels of unit operations. To avoid thermal stress‐induced failures, their transient response needs to be analyzed. In this work, a modular‐hierarchical model for FTHE dynamics is presented and applied to selected transient operating scenarios.